Characterization of initial current pulses in negative rocket‐triggered lightning with sensitive magnetic sensor. Issue 9 (5th September 2016) - Lu, Gaopeng; Zhang, Hongbo; Jiang, Rubin; Fan, Yanfeng; Qie, Xiushu; Liu, Mingyuan; Sun, Zhuling; Wang, Zhichao; Tian, Ye; Liu, Kun
Abstract: We report the new measurement of initial current pulses in rocket‐triggered lightning with a broadband magnetic sensor at 78 m distance. The high sensitivity of our sensor makes it possible to detect weak ripple deflections (as low as 0.4 A) that are not readily resolved in the typical measurements of channel‐base current in rocket‐triggered lightning experiments. The discernible magnetic pulses within 1 ms after the inception of a sustained upward positive leader from the triggering wire can be classified into impulsive pulses and ripple pulses according to the discernibility of separation between individual pulses. The time scale (usually >20 µs) of ripple pulses is substantially longer than the leading impulsive pulses (with time scales typically <10 µs), and the amplitude is significantly reduced, whereas there is no considerable difference in the interpulse pulse. Along with our previous finding on the burst of magnetic pulses during the initial continuous current in rocket‐triggered lightning, the new measurements suggest that the stepwise propagation might be a persistent feature for the upward positive leader in rocket‐triggered lightning, and the stepping of positive leader early in triggered lightning could be characterized with the observation of ripple pulses. The precedence of impulsive magnetic pulse measured at 78 m range relative to the arrival of corresponding current pulse at the channel base indicates that the ionization wave launched by individual stepping of positive leader propagates downward along the triggering wire at a mean velocity of 1.23 × 10 8  m/s to 2.25 × 10 8  m/s. Key Points: New measurement for initial current pulses in triggered lightning with sensitive magnetic sensor Detection of ripple pulses not readily identified in channel‐base current measurements in SHATLE New method to estimate the velocity of ionization wave launched by positive leader stepping